2006
DOI: 10.1210/en.2005-1235
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Binds to Protein Disulfide Isomerase and Inhibits Its Enzymatic and Hormone-Binding Activities

Abstract: Bisphenol A [2,2-bis-(4-hydroxyphenyl) propane; BPA] is a versatile industrial material for plastic products, but is increasingly being recognized as a pervasive industrial pollutant as well. Accumulating evidence indicates that the environmental contaminant BPA is one of the endocrine-disrupting chemicals that potentially can adversely affect humans as well as wildlife. To define the molecular aspects of BPA action, we first investigated the molecules with which it physically interacts. High BPA-binding activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 57 publications
7
81
0
1
Order By: Relevance
“…PDI is believed to act as a buffer for these hormones in cells. PDI is of interest because bisphenol A has been reported to bind to the T 3 binding sites of PDI with 10 to 100-fold lower affinity than T 3 (Hiroi, 2006) and inhibit the binding of T 3 to PDI when bound. PDI immunoreactivity was increased in the neocortex of bisphenol A treated fetuses from GD 12.5-GD 16.5 and in subplate cells at GD 14.5.…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
“…PDI is believed to act as a buffer for these hormones in cells. PDI is of interest because bisphenol A has been reported to bind to the T 3 binding sites of PDI with 10 to 100-fold lower affinity than T 3 (Hiroi, 2006) and inhibit the binding of T 3 to PDI when bound. PDI immunoreactivity was increased in the neocortex of bisphenol A treated fetuses from GD 12.5-GD 16.5 and in subplate cells at GD 14.5.…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
“…BPA changed immune response as it increased gene expression of INF-γ and increased IgG and IgA. In some studies [4,26,27] reported that BPA has multiple actions on patterns of cytokine and antibody production, response to infection, and autoimmune disease progression, T cell subsets, B cell functions, and dendritic cell and macrophage biology. The immunological activities of BPA may be mediated through estrogen receptor signaling, arylhydrocarbon receptor, and the peroxisome proliferator-activated receptor family of nuclear receptors [5] .…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades an increasing interest can be observed on biological effects of this compound. Most studies on endocrine disrupters including bisphenol A have been focused on reproductive toxicology and carcinogenesis [2][3][4][5] . It acts as endocrine disrupter with estrogenic activities in the body.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested previously that BPA functions either estrogenically or anti-estrogenically when binding in vitro to estrogen receptor α in competition with estradiol [11]. The relative binding affinity of BPA to estrogen receptor α is known to be more than 1000 times weaker than that of estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol A (BPA) is a small estrogenic monomer that is polymerized to produce polycarbonate plastic resins that are used to line metal cans [11,12]. BPA is also used in other types of plastic, such as polyvinyl chloride (PVC), used in the manufacture of medical tubing, toys and water pipes, and polyethylene terephthalate (PET), which is used in soda and mineral water bottles.…”
Section: Introductionmentioning
confidence: 99%